SIFAT PEMESINAN JENIS KAYU JAWA BARAT - Osly Rachman; Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1987)
This paper presents  the result of test on machining properties  of 28 wood species from  Bogor and Sukabumi, West Java.  The test method used was the modified  ASTM  D-1666 described in the Forest Products  Research Institut  Report No.  160 (1982).   The samples  (25 pieces/species) were dried  to equilibrium moisture  content condition (15  to  18%).  The machining  properties   investigated   were planning, shaping, boring, mortising,  turning and sanding.The species that have good or very good machining properties  are kobari, pasang jambe,  pasang beureum,  mahoni  daun lebar, pentadesma, cloropora,  eucalyptus,  meranti  batu,  pinus  I, mahoni,  mahagoni  and pinus  III.  Species such  as kelumpang,  entorolobium   and  cecropia  are consistenlly poorer. The other species are good in some properties  and fair or poor  in others.